A re-description of rare alpheid shrimp Amphibetaeus jousseaumei (Coutière, 1896) and escription of a new species of the genus Athanopsis Coutière, 1897(Crustacea: Decapoda: Alpheidae) from Iranian coast of the Persian Gulf - Marin, Ivan; Sheibani, Raheleh; Sari, Alireza (Zootaxa, 2014)
A new record of rare alpheid shrimp Amphibetaeus jousseaumei (Coutière, 1896) (Decapoda: Caridea: Alpheidae) is presented based on material collected from Qeshm Island, Iran, the Persian Gulf. This is the first record of the species for the Iranian waters as well as the second record and re-description of A. jousseaumei from its original description given by Coutière (1896). Besides, a new alpheid shrimp species Athanopsis tarahomii sp. nov. is described from the same locality. The new species can be clearly separated from all remaining species of the genus Athanopsis by deep rostrum curved downward and the presence of well marked blunt extra-cornea tooth on carapace.